1991
DOI: 10.1007/bf00226722
|View full text |Cite
|
Sign up to set email alerts
|

pEmu: an improved promoter for gene expression in cereal cells

Abstract: A recombinant promoter, pEmu, has been constructed to give a high level of gene expression in monocots. It is based on a truncated maize Adh1 promoter, with multiple copies of the Anaerobic Responsive Element from the maize Adh1 gene and ocs-elements from the octopine synthase gene of Agrobacterium tumefaciens. The pEmu promoter was one of 12 different promoter constructs that were linked to the β-glucuronidase (GUS) marker gene. Promoter activity was measured 48 h after introduction of the constructs into pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
73
0
3

Year Published

1995
1995
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(81 citation statements)
references
References 28 publications
5
73
0
3
Order By: Relevance
“…It contains also the reporter GUS gene controlled by the Emu promoter and the Nopaline Synthetase (NOS) terminator. The Emu promoter is a recombinant promoter based on truncated maize Adh1 promoter, with multiple copies of the Anaerobic Responsive Element from the maize Adh1 gene and OCS-elements from the octopine synthase gene of A. tumefaciens (Last et al, 1991).…”
Section: Pemugn Plasmidmentioning
confidence: 99%
“…It contains also the reporter GUS gene controlled by the Emu promoter and the Nopaline Synthetase (NOS) terminator. The Emu promoter is a recombinant promoter based on truncated maize Adh1 promoter, with multiple copies of the Anaerobic Responsive Element from the maize Adh1 gene and OCS-elements from the octopine synthase gene of A. tumefaciens (Last et al, 1991).…”
Section: Pemugn Plasmidmentioning
confidence: 99%
“…From the wide range of regulatory sequences available it could be expected that sequences shown to drive high levels of expression in other monocotyledenous species would function well in onions. Sequences such as the maize alcohol dehydrogenase (ADH) promoter and intron (Callis et al 1987), the rice actin promoter (ACT1-D) (McElroy et al 1990), the ubiquitin (UBI) promoter (Christensen et al 1992), the chimeric promoter EMU (Last et al 1991), or gemminivirus promoter sequences such as those isolated by Zhan et al (1993). Initial results in our laboratory (Eady et al 1995b) have demonstrated that many of these promoters and the alliinase promoter isolated from onion (Gilpin et al 1994) fail to function as efficiently as the CaMV 35 S promoter suggesting that onion is responding best to promoters more commonly used in dicoty ledenous transformation systems.…”
Section: Regulatory Sequencesmentioning
confidence: 99%
“…The most widely used particle gun is the PDS-1000/He device (Kikkert, 1993) (Luo and Wu, 1988), and shaking cells with small silicon carbide crystals (whiskers) in a DNA solution Frame et al, 1994). The last method is experimentally very simple and does not require any expensive equipment; the general applicability of the other methods (assessed by Potrykus, 1990) (Grimsley et al, 1987) and recently transgenic rice plants with stably integrated, Agrobacterium-transferred DNA have been described (Chan et al, 1993;Hiei et al, 1994 2) The hptI gene isolated from E coli confers resistance to hygromycin (Gritz and In a few cases, transgenic material has been selected by a sublethal GUS staining (Omirulleh et al, 1993;Arencibia et al, 1995 (Omirulleh et al, 1993), by insertion of other transcriptional enhancers (Olive et al, 1990;Last et al, 1991) or by combination with intron sequences (Tanaka et al, 1990; see also below). In mature plants, the promoter may exhibit some tissue specificity for the vascular tissue but it is also reported to be active in more or less all cells (Battraw and Hall, 1990;Terada et al, 1990 (Toki et al, 1992;Weeks et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…This is based on experiments in protoplasts that showed that the presence of introns can enhance gene expression up to 100-fold (Callis et al, 1987;McElroy et al, 1990;Last et al, 1991;Maas et al, 1991;Chibbar et al, 1993). It should be noted that these data are frequently derived from comparisons of constructs that varied by more than just the presence or absence of an intron and that very different stimulation factors have been observed in different expression systems (Oard et al, 1989;Vasil et al, 1989;Last et al, 1991;Luehrsen and Walbot, 1991;Rathus et al, 1993). The effect of an intron can drastically depend on the promoter with which it is combined (Last et al, 1991) (Ingelbrecht et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation